2014
DOI: 10.1007/s11999-014-3471-7
|View full text |Cite
|
Sign up to set email alerts
|

Terrible Triad Injuries of the Elbow: Does the Coronoid Always Need to Be Fixed?

Abstract: Background The ''terrible triad'' of the elbow is a complex injury that can lead to pain, stiffness, and posttraumatic arthritis if not appropriately treated. The primary goal of surgery for these injuries is to restore stability of the joint sufficient to permit early motion. Although most reports recommend repair and/or replacement of all coronoid and radial head fractures when possible, a recent cadaveric study demonstrated that type II coronoid fractures are stable unless the radial head is removed and not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(51 citation statements)
references
References 18 publications
0
48
0
3
Order By: Relevance
“…Type i fractures account for about 82% of injuries and are treated conservatively. The indications for surgical treatment are fractures of ii-iV type with the displacement of fragments, limitation of mobility, and elbow instability [1,12,17,18]. Factors that influence the decision to implant a radial head prosthesis include a large number of fractured fragments (more than 3 fragments), the risk of osteonecrosis after osteosynthesis, fracture of the head associated with dislocation within the radial-ulnar joint, and the patient's age (in younger patients, osteosynthesis of the broken head is preferred) [1,8,12,14].…”
Section: Discussionmentioning
confidence: 99%
“…Type i fractures account for about 82% of injuries and are treated conservatively. The indications for surgical treatment are fractures of ii-iV type with the displacement of fragments, limitation of mobility, and elbow instability [1,12,17,18]. Factors that influence the decision to implant a radial head prosthesis include a large number of fractured fragments (more than 3 fragments), the risk of osteonecrosis after osteosynthesis, fracture of the head associated with dislocation within the radial-ulnar joint, and the patient's age (in younger patients, osteosynthesis of the broken head is preferred) [1,8,12,14].…”
Section: Discussionmentioning
confidence: 99%
“…None of the patients received fixation of the coronoid fracture, required MCL repair, or had an external fixator applied for residual stability. At an average follow-up of 41 months, Papatheodorou et al [22] reported good outcomes with no cases of late instability.…”
Section: Terrible Triadmentioning
confidence: 99%
“…In contrast, type 3 coronoid fractures were unstable, even with intact collateral ligaments and radial head [21]. Papatheodorou et al [22] evaluated the clinical outcomes in patients with terrible triad injuries and Regan-Morrey types 1 and 2 coronoid fractures. In their series, all patients underwent either radial head fixation or arthroplasty and a LCL repair.…”
Section: Terrible Triadmentioning
confidence: 99%
“…Einigkeit besteht über die Rekonstruktions-/Ersatznotwendigkeit des Radiuskopfs und die Naht des LCL [10]. Inwieweit die Koronoidspitze und damit die vordere Gelenkkapsel readaptiert werden soll [11], ob das MCL bei persistierender Instabilität direkt vernäht oder ob eine Sicherung der Gelenkführung durch einen Bewegungsfixateur genügt, um den medialen Eingriff zu ersparen, wird basierend auf retrospektiven Studien und biomechanischen Arbeiten unterschiedlich postuliert [12][13][14]. Abb.…”
Section: Introductionunclassified